What are digital media?. (June 2021) - Bateman, John A.
Abstract: This essay addresses the nature of so–called 'digital media' in a literacy context from the perspectives of semiotics, theories of the 'medium', and computation. It argues that most accounts that attempt to work with some notion of 'digital media' anchor themselves insufficiently in semiotics and computation and the essential combination of these that is necessary when discussing digital media as an object of study. This weakens approaches, particularly when the concern is to develop ways of teaching engagement with contemporary communication practices at any level, i.e., improving 'digital literacies' of various kinds. Achieving more robust foundations is important for interventions which are not only more effective but also sustainable, minimizing the danger of obsolescence with each new technological turn of the screw. Foundations are also essential for a more balanced perspective on learning situations that does not dichotomize allegedly 'digital' and 'non–digital' practices and skills. Many such boundaries are deeply misleading and so unnecessarily compartmentalize thinking and restrict the application of relevant research results and methods. The focus of this essay is therefore to consider how a closer examination of media and their development, combined with the contributions made by information technologies, may help articulate notions of digital media that are more supportive of productive engagements with research and issues of literacy.